Flood Discharge Reduction Analysis of Ciawi and Sukamahi Dry Dams - Dasylva, Iqbal Zaenal; Sumiadi, Sumiadi; Prasetyorini, Linda; Beselly, Sebrian Mirdeklis (Fakultas Teknik, Universitas Brawijaya, 2025)
Floods are a natural disaster often experienced by the people of Indonesia, especially in Jakarta. In 2022, the government inaugurated the upstream area of ​​the Ciliwung River Basin. The research provides an in-depth analysis of the reductions achieved by the two dry dams across a range of return periods (Q), specifically 2, 5, 10, 25, 50, and 100 years, highlighting their performance in reducing peak flow volumes and their effectiveness in flood risk management under varying hydrological conditions. Currently, both do not have intake on their conduit channels. With this research, it is hoped that it can be determined whether or not the reduction results will be optimal by adding intake to their conduit channels. The results and analysis obtained on the Ciawi dry dam, namely Q2 can reduce up to 73.49%; Q5 can reduce up to 76.17%; Q10 can reduce up to 78.49%; Q25 can reduce up to 80.33%; Q50 can reduce up to 66.93%; and Q100 can reduce up to 54.98% while for the results and analysis of reduction in the Sukamahi dry dam for Q2 can reduce up to 78.40%; Q5 can reduce up to 82.24%; Q10 can reduce up to 83.38%; Q25 can reduce up to 84.41%; Q50 can reduce up to 84.94%; and Q100 can reduce up to 85.26%.